Implementation of in House Training using the Teams Application to Improve Teacher Competence in Distance Learning at SDN 2 Pengadegan in Odd Semester in the 2021/2022 Academic Year - Marfuah Marfuah; Yahya Sudarya; Efi Nursetiasih (Proceedings Series on Social Sciences & Humanities, 2023)
Realizing educational goals is one of the visions and missions of a school. Class teachers are the front line in realizing educational goals. With the Covid-19 pandemic and the online school policy, the school principal has made a suitable strategy to improve teacher competence, one of which is in-house training using the Teams application. The research method used in this research is school action research. Data collection techniques using observation and documentation. The results of this study implementing in-house training using the Teams application can increase teacher competence in distance learning at SDN 2 Pengadegan in the odd semester of the 2021/2022 academic year.